On the come up eaudiobook - Thomas, Angie (2019)
Don't miss this audiobook, Audible's Young Adult Audiobook of the Year and an Audie Award finalist! The YA love letter to hip-hop—streaming on Paramount+ September 23, 2022! Starring Sanaa Lathan (in her directorial debut), Jamila C. Gray, Da'Vine Joy Randolph, Lil Yachty, Method Man, Mike Epps, GaTa (Davionte Ganter), Miles Gutierrez-Riley, Titus Makin Jr., and Michael Anthony Cooper Jr. #1 New York Times bestseller · Seven starred reviews · Boston Globe-Horn Book Award Honor Book Sixteen-year-old Bri wants to be one of the greatest rappers of all time. Or at least win her first battle. As the daughter of an underground hip hop legend who died right before he hit big, Bri's got massive shoes to fill. But it's hard to get your come up when you're labeled a hoodlum at school, and your fridge at home is empty after your mom loses her job. So Bri pours her anger and frustration into her first song, which goes viral . . . for all the wrong reasons. Bri soon finds herself at the center of a controversy, portrayed by the media as more menace than MC. But with an eviction notice staring her family down, Bri doesn't just want to make it—she has to. Even if it means becoming the very thing the public has made her out to be. Insightful, unflinching, and full of heart, On the Come Up is an ode to hip hop from one of the most influential literary voices of a generation. It is the story of fighting for your dreams, even as the odds are stacked against you; and about how, especially for young black people, freedom of speech isn't always free. "For all the struggle in this book, Thomas rarely misses a step as a writer. Thomas continues to hold up that mirror with grace and confidence. We are lucky to have her, and lucky to know a girl like Bri."—The New York Times Book Review Hear about more of life in Garden Heights from Angie Thomas in The Hate U Give and Concrete Rose.